(untitled) (Research, Society and Development, 2020)
This article presents, in general lines, the state of knowledge on research that deals with the educational principle teaching with research in initial teacher training. In view of the scope and dimension of the state of knowledge of this subject, this research work analyses a current conception of the educational principle with research, as well as challenges and perspectives. Consisting of a qualitative and dialectical perspective, it was produced by means of a bibliographical research and analysis of works presented at the annual meetings of the National Association for Research in Education (ANPED), concentrated in working groups called "GT 04 - Didactics" and "GT 08 - Teacher Training". Involved in this analysis, it points out fundamentals that can guide educational practices characterized by the aforementioned principle, presenting elements that aim to contribute to teaching, research and learning activities in initial teacher training courses. They point out indicators for the revision of the pedagogical projects of the courses that form these teachers and possible paths for the development of a process of teaching and learning, where through teaching knowledge is also produced (through research).